P212 PROGNOSTIC ROLE OF ACUTE MYOCARDIAL INFARCTION DIAGNOSTIC CRITERIA IN NON–ST SEGMENT ELEVATION MYOCARDIAL INFARCTION. (18th May 2022) - Sansonetti, A; Armillotta, M; Amicone, S; Impellizzeri, A; Angeli, F; Fabrizio, M; Stefanizzi, A; Bergamaschi, L; Magnani, I; Rinaldi, A; Foà, A; Galiè, N; et al.
Abstract: Background: Although the majority of patients with NSTEMI share similar risk factors and similar pathophysiology, their outcomes differ considerably. The Fourth Universal Definition of Myocardial Infarction (UDMI) defined acute myocardial infarction (AMI) by an acute myocardial injury together with clinical evidence of acute myocardial ischaemia. However, the prognostic role of each single diagnostic criteria has never been explored. Purpose: To evaluate the prognostic role of the different diagnostic criteria of AMI according to the Fourth UDMI in NSTEMI patients. Methods: We enrolled all consecutive patients with AMI undergoing coronary angiogram at our Centre. We used a combination of criteria, according to the current ESC guidelines, to meet the diagnosis, namely the detection of an increase and/or decrease of high–sensitivity cardiac troponin I, with at least one value above the 99th percentile of the upper reference limit and at least one of the following: symptoms of ischaemia; ECG changes (new ST–T changes or new LBBB); development of pathological Q waves in the ECG; echocardiographic evidence of new loss of viable myocardium or new regional wall motion abnormality. Patients with STEMI and very high risk NSTEMI were excluded. A composite endpoint of all–cause mortality, re–hospitalization for heart failure, and myocardial reinfarction was collected. The predictive value of diagnostic criteria alone and their association were evaluated using Kaplan–Meier survival curves and subsequent Cox–regression analysis to find independent predictors of adverse events. Results: 2791 patients with NSTEMI were evaluate. At admission 196 had clinical criteria alone, 187 had clinic + ECG and 829 had clinic + ECG + echo. The total number of events was 689. The median follow–up was 23.3±14.5 months. We found that patients with clinical criteria alone had a better prognosis at 2 years follow–up (p < 0.001). No other significant prognostic correlation was found. Multivariable Cox–regression model demonstrated that clinical criteria was the only independent predictor of better prognosis in patients with NSTEMI (HR = 0.48; CI 95% 0.31–0.74; p < 0.001). Conclusions: Our data suggest that in NSTEMI the prognosis is considerably better if clinical criteria alone is present at admission. We hypothesize that the absence of electrocardiographic and echocardiographic alterations in NSTEMI could indirectly indicate smaller infarct sizes or other causes of acute myocardial injury.